(untitled) (Research, Society and Development, 2024)
Despite vultures’ vital role in nature, they are insufficiently addressed in Brazilian educational content, leading to misconceptions about these scavenging birds. With educators neglecting the topic, students rely on their families, social circles, and the media for information, perpetuating misunderstandings. To rectify this and enhance comprehension of vultures’ ecological importance, this study examines student perceptions through prior knowledge (PK) analysis. The study involved high school graduates up to 2019 and first- and second-semester college Biology students in Pernambuco, Brazil. A questionnaire with context-rich, thought-provoking questions was employed to stimulate knowledge retrieval. Data was analyzed using Laurence Bardin’s content analysis. Findings revealed students’ limited knowledge about vulture species. When asked to explain color variations in vultures’ heads, some students resorted to prior knowledge related to intraspecific dominance, sexual dimorphism, camouflage, and diet from other bird species. Some perceived vultures as environmental cleaners, while others associated them with carcass decomposition and disease transmission, along with negative aesthetic and hygienic attributes. It’s imperative that students not only study textbook-highlighted species but also gain insights into local fauna and its environmental significance. This broader understanding can rectify misconceptions and promote the vital ecological role vultures play in maintaining the balance of ecosystems.